A study on factors that contribute to academic achievement among Bachelor in Administrative Science (Hons.) Students at Universiti Teknologi Mara, Malacca City Campus / Nur Syahirah Izani and Nurul Izni Diyana Nor Azlan - Izani, Nur Syahirah; Nor Azlan, Nurul Izni Diyana (Faculty of Administrative Science and Policy Studies, 2012)
University students, especially Bachelor in Administrative Science (BAS), (Hons) perceived as a group considered intellectual, full of spirit, well educated and involved with professional matters. The students usually involve with various division of focus in learning such as politics, economy, administration, law, accounting and others. In addition, the students can be classified as group that has better competitive advantage compared to other courses because of their wide learning scope. In order to identify the factors contribute to the academic achievement among BAS students, to examine the significant relationship between factors and to study the significant different between demographic factor (semester) and the performance in academic achievement, the study was conducted in Universiti Teknologi Mara (UiTM), Malacca City Campus. The sampling technique that has been used is cluster sampling. The respondents of the study were selected using cluster sampling while random samples of 109 respondents consist of semester 2, semester 3, semester 4, semester 5 and semester 6 were selected based on one faculty. According to the findings, it shows that all the three factors which are learning style, academic facilities and students and lecturers relationship contribute to the academic achievement among Bachelor in Administrative Science (Hons) students in Universiti Teknologi Mara (UiTM), Malacca City Campus.